Ampicillin removal by polyvinylidene diflouride (PVDF), polyethersulfone (PES) and nylon for membrane bioreactor application - Labinghisa, Ruby S. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Micro-pollutants comprising of pharmaceutically active compounds (PhACs) are usually not degraded or removed in conventional wastewater treatment systems and are persistent in aquatic environment.. This study determined the rejection of ampicillin by hydrophobic and hydrophilic membranes, the effects of operational parameters such as flow rate (1.4 and 2.2 mL/min), influent concentration (40, 70 and 100 ppb) and the extent of biodegration and adsorption of ampicillin in batch membrane bioreactor with and without nitrification. Ampicillin removal was higher in the bioreactor where nitrification occurred and at lower concentration and flow rates. The results showed that membrane bioreactor (MBR), with combined biological degradation and membrane filtration is a viable system for ampicillin removal. Besides biodegradation in the bioreactor, the cake layer deposited over the membrane surfaces played an important role in AMP rejection. A big part of the removal by the membrane system was attributed to the sieving and/or adsorption onto the cake layer. Keyword: biodegradation, COD, micro-pollutant, pharmaceutical, rejection
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Membrane reactors; Pharmaceutical industry -- Environmental aspects; Ampicillin -- Biodegradation